2021
DOI: 10.3390/s21041505
|View full text |Cite
|
Sign up to set email alerts
|

Load Resistance Optimization of Bi-Stable Electromagnetic Energy Harvester Based on Harmonic Balance

Abstract: In this study, a semi-analytic approach to optimizing the external load resistance of a bi-stable electromagnetic energy harvester is presented based on the harmonic balance method. The harmonic balance analyses for the primary harmonic (period-1T) and two subharmonic (period-3T and 5T) interwell motions of the energy harvester are performed with the Fourier series solutions of the individual motions determined by spectral analyses. For each motion, an optimization problem for maximizing the output power of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It was demonstrated that the optimal load resistance strongly depended on the oscillation frequency of the interwell motion rather than on the forcing frequency of excitation. Although harmonic distortions in the interwell motions of the 1-DOF systems were not significant [26,27], it can be readily deduced that high-order frequency components are important in the optimization of the external load resistance. Thus, the impedance matching technique is possibly undesirable and inappropriate for the load resistance optimization of the 2-DOF MCBEH when certain high-order harmonics are significant in response (e.g., the third-harmonic distortion of beam 2 presented later in this study).…”
Section: Contribution Of This Studymentioning
confidence: 96%
See 1 more Smart Citation
“…It was demonstrated that the optimal load resistance strongly depended on the oscillation frequency of the interwell motion rather than on the forcing frequency of excitation. Although harmonic distortions in the interwell motions of the 1-DOF systems were not significant [26,27], it can be readily deduced that high-order frequency components are important in the optimization of the external load resistance. Thus, the impedance matching technique is possibly undesirable and inappropriate for the load resistance optimization of the 2-DOF MCBEH when certain high-order harmonics are significant in response (e.g., the third-harmonic distortion of beam 2 presented later in this study).…”
Section: Contribution Of This Studymentioning
confidence: 96%
“…However, the use of this impedance-matching technique for bistable energy harvesters is based on the oversimplification that only the fundamental frequency component of response is considered in the load resistance optimization [25]. In previous works [26,27], the load resistance optimizations of the 1-DOF bistable piezoelectric and electromagnetic energy harvesters were performed for primary harmonic and subharmonic interwell motions. It was demonstrated that the optimal load resistance strongly depended on the oscillation frequency of the interwell motion rather than on the forcing frequency of excitation.…”
Section: Contribution Of This Studymentioning
confidence: 99%
“…Kunz et al [7] focused their efforts on novel methods to assess the performance of these harvesters in terms of power flow. Bae and Kim [8], on the other hand, approached sensor performance issues in terms of load resistance optimisation for a bi-stable system. Okosun et al [9] addressed one of the core sustainable development goals, the availability of drinking water, and experimentally demonstrated how energy harvesting patches can be used for pipeline leak detection, creating a respective benchmark.…”
mentioning
confidence: 99%